Crystal structure and Hirshfeld surface analysis of the fungicide metconazole - Thaluru M. Mohan Kumar; Chaluvarangaiah Sowbhagya; Hemmige S. Yathirajan; Sean Parkin (Acta Crystallographica Section E: Crystallographic Communications)
Metconazole is a systemic triazole fungicide that inhibits the ergosterol biosynthesis pathway. It is widely used in agriculture to control fungal infections, including rusts, fusarium and septoria diseases. The molecular structure is a three-ring system, namely, 5-(4-chlorobenzyl)-2,2-dimethyl-1-(1H-1,2,4-triazol-1-ylmethyl)cyclopentan-1-ol, C17H22ClN3O, consisting of a cyclopentan-1-ol with 1,2,4-triazol-1-ylmethyl, gem-dimethyl and 4-chlorobenzyl groups attached at the 1-, 2- and 5-positions of the cyclopentanol ring. It has two stereocentres (cyclopentanol positions 1 and 5) leading to four stereoisomers, with the (1S,5R) form being the most bioactive. Despite its agricultural significance, detailed crystallographic data remain scarce. This study reports the crystal structure and Hirshfeld surface analysis of racemic cis-metconazole [(1S,5R)/(1R,5S)], determined in the monoclinic space group P21/c with two independent molecules in the asymmetric unit (Z′ = 2). Both exhibit similar conformations, with minor differences in the cyclopentanol ring puckering and the torsion angles between the three rings. The crystal packing consists of 21-screw-related hydrogen-bonded chains parallel to the b axis, with additional weak C—H...N and C—H...Cl contacts linking adjacent molecules. Hirshfeld surface analysis indicates that intermolecular interactions are dominated by contacts involving hydrogen (96.1 and 96.7% for the two molecules).